2018
DOI: 10.1108/jmp-12-2016-0393
|View full text |Cite
|
Sign up to set email alerts
|

Leading organizational transformation: an action research study

Abstract: 2Purpose -This study addresses a specific gap in the literature that centers on individual perspective 3 of leadership within the context of organizational transformation. It explores synergies between 4 leadership, analyzed as a combination of individual and plural perspectives, and managerial drivers 5 relating to organizational transformation (communicating, mobilizing, and evaluating), with a focus 6 on capturing the essence of the context. 7Design/methodology/approach -The study examines a complex organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…This study has provided a theoretical implication by giving further empirical evidence on resource-based view theory, where talent and knowledge management have been hypothesized as a resource for university transformation. Similarly, the results showed that university transformation involves ongoing direction reviews, structure, systems, strategies, values, personnel competencies, and skills to adapt to the changing organizational environment to promote growth and new knowledge (Burnes and Cooke, 2012;Canterino et al, 2018). Previous studies also emphasize three main managerial drivers related to the transformation process: communication, mobilizing process strategy, and evaluating structure (Battilana et al, 2010).…”
Section: Discussionmentioning
confidence: 87%
“…This study has provided a theoretical implication by giving further empirical evidence on resource-based view theory, where talent and knowledge management have been hypothesized as a resource for university transformation. Similarly, the results showed that university transformation involves ongoing direction reviews, structure, systems, strategies, values, personnel competencies, and skills to adapt to the changing organizational environment to promote growth and new knowledge (Burnes and Cooke, 2012;Canterino et al, 2018). Previous studies also emphasize three main managerial drivers related to the transformation process: communication, mobilizing process strategy, and evaluating structure (Battilana et al, 2010).…”
Section: Discussionmentioning
confidence: 87%
“…Although evidence is limited, previous findings show that a plural approach to leadership when dealing with change is important, and that certain patterns of distributed leadership have a positive effect on organizational change (Buchanan et al, 2007;Heck & Hallinger, 2010;Fitzgerald et al, 2013;Canterino, Cirella, & Shani, 2018). Since organizations have become increasingly projectand knowledge-based, involving professional work and a need for innovation, leaders must be able to deal with collective efforts in which individuals contribute to establishing and developing a common purpose and vision (Bolden, 2011).…”
Section: Distributed Leadership and Change Mobilization: Hypothesis Developmentmentioning
confidence: 99%
“…Indeed, the complexity of the phenomenon and the exploratory nature of the investigation suggest adopting a qualitative research approach and conducting interviews and observation on inspiring cases to dig deeper into this emerging approach to innovation (Spradley, 2016). Furthermore, the adoption of such methodology in directly get empathy with users by ethnographically observing them allows us to deal with the "how" question underpinning the research (Canterino et al, 2018). In particular, the study aims to enrich both practitioner and researcher knowledge on the practical way the Design Sprint methodology can be adopted not only by start-ups but also by other companies.…”
Section: Research Methodology 41 the Research Methodsmentioning
confidence: 99%